Impact of Liquidity and Basel III Regulation on Bank Profitability - Duong Thuy Nguyen; Trang Thi Thu Nguyen; Oanh Thi Kim Nguyen (Ital Publication, 2026)
This study examines the relationship between liquidity on bank profitability in the context of Vietnamese commercial banks, focusing on the moderating effect of Basel III regulations. Using data from 26 commercial banks listed on Vietnam’s stock exchanges between 2012 and 2023, the research employs multiple econometric models, including OLS, FEM, REM, and Generalized Method of Moments (GMM), to explore the effects of liquidity measures such as liquid assets to total assets (LATA) and the liquidity transformation gap (TLGAP) on key profitability indicators; Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). The findings suggest a negative relationship between liquidity and profitability of commercial banks in Vietnam, with higher liquidity levels constraining profit generation. Additionally, the study reveals that adopting Basel III regulatory standards, particularly its liquidity and capital requirements, mitigates the negative effects of liquidity on the profitability of commercial banks in Vietnam. The results highlight the trade-off commercial banks face between maintaining sufficient liquidity for financial stability and optimising profitability. This research contributes to the understanding of liquidity management in emerging markets, emphasising the role of Basel III in balancing regulatory compliance with financial performance.